1994
DOI: 10.1016/0370-1573(94)90040-x
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-energy semileptonic probes of the hadronic neutral current

Abstract: IIII!_ IIII1_ IIII1_ IIII1_ IIII1_INTEI{ME[_IATE ENERGY SEMILEPT()NIC PROIBES ()F THE HADRONIC NEUTRAL CURRENT' The Continuous Electron Beam Accelerator Facility Theory Group Preprint Series M. J MusolP, '1'. W. I)onnelly l', J. l)ubach', .% .I I',_lh),'k 't, S. Kowalski", and E. J l},'i._(J-Additional copies are available from the authors. _ (;enter for Theoretical I'hysics, Lal)oratory fc_rNuclear Sci_mc_' and I)ei,artlJJent of Physics, Ma.ssachusctts Institute of 'l_chnoiogy, (_.ai,lbridgc, M_L_achusetl.s 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
415
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(426 citation statements)
references
References 196 publications
8
415
0
3
Order By: Relevance
“…The 4 He nucleus is spin zero, parity even, and isoscalar. The PV asymmetry takes a much simpler form [4],…”
Section: A and R T =0mentioning
confidence: 99%
See 3 more Smart Citations
“…The 4 He nucleus is spin zero, parity even, and isoscalar. The PV asymmetry takes a much simpler form [4],…”
Section: A and R T =0mentioning
confidence: 99%
“…Nuclear corrections are only relevant for nonhydrogen targets. For the two 4 He measurements, according to Ref. [24], 3% is assigned as the fractional theoretical uncertainty of A nvs .…”
Section: Global Analysis a A Nvs And Theoretical Uncertaintiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Early polarized deep-inelastic scattering (DIS) experiments suggested that a surprisingly large fraction of the proton's spin might be carried by strange quarks [1], in contrast to the naive quark model expectations [2]. Recognition that the spatial distributions of strange quarks and antiquarks could be different further motivated searches for strange contributions to the nucleon's electroweak form factors [3][4][5][6][7][8]. Dedicated programs of strange form factor measurements through parityviolating electron scattering at Jefferson Lab and other facilities [9][10][11] subsequently yielded very precise determinations of both the strange electric and magnetic form factors of the nucleon [12], enabling rigorous comparisons with lattice QCD and chiral effective theory [13,14], as well as fundamental tests of the Standard Model [15].…”
Section: Introductionmentioning
confidence: 99%